Influence of vegetation on the removal of heavy metals and nutrients in a constructed wetland - Maine, Maria Alejandra (2009)
A free water surface wetland was built to treat wastewater containing metals (Cr, Ni, Zn) and nutrients from a tool factory in Argentina. Water, sediment and macrophytes were sampled in the inlet and outlet area of the constructed wetland during three years. Three successive phases of vegetation dominance were developed and three different patterns of contaminant retention were observed. During the Eichhornia crassipes dominance, contaminants were retained in the macrophyte biomass; during the E. crassipes + Typha domingensis stage, contaminants were retained in the sediment and in the T. domingensis dominance stage, contaminants were retained in sediment and in the macrophyte biomass. Removal efficiency was not significantly different among the three vegetation stages, except for NH4+ and i-Pdiss. Because of its highest tolerance, T. domingensis is the best choice to treat wastewater of high pH and conductivity with heavy metals, a common result from many industrial processes.